Hyaluronic acid rheological properties of Synvisc and Suplasyn for intraarticular injection In osteoarthritis - Abd. Rahim, Nour Elhuda; Zulkifly, Ahmad Hafiz; Mohamed, Farahidah; Ku Zaifah, Norsidah (2011)
Current pharmacological treatments for osteoarthritis are analgesics and intraarticular injection of hyaluronic acid (IAHA). Rheological measurements were performed on the viscosupplements to evaluate viscosity and dynamic responses with the aim to compare Synvisc (high molecular weight IAHA) with Suplasyn (low molecular weight IAHA). Both are widely used in the conservative treatment of osteoarthritis. The viscosity and dynamic rheology were analysed at different temperatures (25, 37 and 40°C) using ThermoHaake rheometer. The dynamic oscillatory testing was used to measure the storage modulus (G') and the loss modulus (G") of IAHA within the linear viscoelastic region. Suplasyn and Synvisc behaved as non-Newtonian shear thinning fluids (pseudoplastic flow type) however Synvisc showed higher viscosity compared to Suplasyn. By increasing the temperatures, the viscosity of the IAHA were reduced. In the dynamic oscillatory testing for viscoleasticity, the LVR of Synvisc was within 0.01-100Hz, meanwhile 0.1-10Hz for Suplasyn. The length of the LVR represented the stability of the microstructure of IAHA, and Synvisc was more stable than Suplasyn. The storage modulus of Synvisc was more than the loss modulus (G'>G") in all temperatures. The elastic like behaviour was more dominant in Synvisc compared to viscous like behaviour. Unlike, Suplasyn, the viscous like behaviour was more pronounced than the elastic like behaviour by showing the loss modulus was more than the storage modulus (G”>G’) in all temperatures. At human body temperature, 37°C, both viscosupplements shared the same pseudoplastic type of non-Newtonian fluid and shear thinning behaviour. However, Synvisc is more elastic compared to Suplasyn probably may be due to its higher molecular weight and cross linking properties.